Best Answer

Assuming that the two equations are:

2y = x + 4 .................................. 1

y = 12 + 3x ............................. 2

multiplying eqn 2 by two and subtracting it from eqn 1 results in:

0 = 5x + 20, then x = -4

Substituting in eqn 2 with x = -4 results in y = 0

then the common intersection point is (-4, 0)

Q: Does 2y x 4 and y 12 3x have a common solution?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

-3x + 2y = 12-3x + 3x + 2y = 3x + 122y = 3x + 122y/2 = 3x/2 + 12/2y = (3/2)x + 6

Both of them are equations!The solution is (x, y) = (2, 1).

(A) 3x + 2y = -2 (B) 6x - y = 6 (A) + 2(B): 3x + 2y + 12x - 2y = -2 + 12 or 15x = 10 or x = 2/3 substitute this value of x in (A) 2 + 2y = -2 2y = -4 and y = -2 Answer: x = 2/3, y = -2

2y + 3x = 0 2y + -3 = 0 2y = 0 + 3 , 2y = 3 y = 3/2 y = 1.5 x = -1

x = 3 and y = 2

Related questions

-3x + 2y = 12-3x + 3x + 2y = 3x + 122y = 3x + 122y/2 = 3x/2 + 12/2y = (3/2)x + 6

3x - 2y = 12 2y + 12 = 3x 2y = 3x - 12 y = 3x/2 - 6 Gradient = 3/2 Y-intercept = -6

3x + 2y = 12 ie 2y = 12 - 3x so y = 6 - 3x/2

No, it has an infinite number of solutions. The coordinates of each and every point on the line 3x + 2y + 4 = 0 is a solution.

3x + 2y + 5 - 3 = 3x + 2y + 2 No further simplification is possible. This is an expression, not an equation so there cannot be a solution.

Both of them are equations!The solution is (x, y) = (2, 1).

rearrange into standard form: first add 2y to each side:3x -2y + 2y = 12 + 2y --> 3x = 12 + 2yThen subtract 12 from each side: 3x - 12 = 12 + 2y - 12 ---> 3x - 12 = 2ynext divide both sides by 2: (3/2)x - (12/2) = (2/2)y(3/2)x - 6 = yso y = (3/2)x -6in y = mx + b, with m as slope and b as y-intercept, so slope(m) is 3/2 = 1.5also the line intersects the y-axis at y = -6

(A) 3x + 2y = -2 (B) 6x - y = 6 (A) + 2(B): 3x + 2y + 12x - 2y = -2 + 12 or 15x = 10 or x = 2/3 substitute this value of x in (A) 2 + 2y = -2 2y = -4 and y = -2 Answer: x = 2/3, y = -2

Which system of inequalities has no solution?A.y > 3x - 1y < 3x - 3B.y > 3x + 3y < 3x + 7C.y > -1y < 2y > 2x - 3re...

3x - 2y and 3x + 2y are in their simplest form. They don't factor.

2y + 3x = 0 2y + -3 = 0 2y = 0 + 3 , 2y = 3 y = 3/2 y = 1.5 x = -1

3x = 2y + 3 3x -3 = 2y +3 -3 3x - 3 = 2y (3x -3)/2 = 2y / 2 y = 1/2 x (3x - 3) 3x = 2y +3 3x - 3x = -3x +2y +3 0 = -3x +2y +3 -1 x (0) = -1 x (-3x +2y +3) 0 = 3x - 2y -3